An innovative konjac glucomannan/κ‐carrageenan mixed tensile gel. (22nd February 2021) - Wu, Di; Yu, Simin; Liang, Hongshan; Eid, Mohamed; Li, Bin; Li, Jing; Mao, Jin
Abstract: BACKGROUND: Konjac glucomannan (KGM) showed a synergistic interaction with κ‐carrageenan (CAR), which led to the formation of a promising compound hydrocolloid gel in the food field (such as jelly). Nevertheless, the mixed gels formed by adding KGM to CAR still displayed defects in gel strength and syneresis, and would hardly meet the quality requirements of some gel foods. However, deacetylated KGM and maltodextrin (MD) have always been used in gel foods and affect their viscosity and rheological properties. RESULTS: In our paper, different amounts of MD were first used to alter the textural properties, and the results showed that both tensile strength and elongation exhibited first an increasing and then a decreasing trend with the increasing MD proportion and achieved a maximum at a final maltodextrin proportion of 4 g kg −1 in the KGM/CAR/MD system. Based on the above results, we further explored the effects of deacetylation degree of KGM on the gel properties of mixed gel system. The results revealed that, compared to the native KGM, the partial deacetylated KGM was capable of significantly improving the tensile strength and elongation of KGM/CAR mixed gel. CONCLUSION: Our study found that the appropriate addition of MD (0.4%) and DKGM were able to alter the tensile properties of KGM/CAR mixed gel, with potential to meet the needs of consumers and further design innovative tensile gel products in the soft gel industry. © 2021 Society of Chemical Industry